Remote infrared thermography in the system of comprehensive diagnostics of the health of military personnel before surgical intervention - Kostrub, Oleksandr; Shukalo, Oleksandr; Dunaevsky, Vadim; Kotovsky, Vitaliy; Tymofeiev, Volodymyr; Nazarchuk, Svitlana (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
A complete and informative diagnosis of the general health of military personnel before surgical intervention is of great importance for its successful implementation. A simple and affordable diagnostic method of radiological diagnostics is the method of remote infrared thermography. Conducting a comprehensive thermographic examination of military personnel before surgical intervention allows for the treatment of those pathological conditions that were detected during the thermographic examination. Objective. To show the possibility and evaluate the diagnostic informativeness remote infrared thermography in the system of comprehensive diagnostic monitoring of the health of military personnel before surgical intervention; to obtain thermographic visualizations of detected pathological changes associated with participation in combat operations. Methods. The work used a domestic thermograph with a temperature sensitivity of 0.07 °C and a ThermaCAM thermograph E 300 FLIR SYSTEM. Observation and control of thermal fields were carried out in the ranges of 3÷5 μm and 8÷14 μm. The examination was carried out during inpatient and outpatient treatment. Results. Received thermographic visualizations detected pathologies: disorders functions breathing; thermal asymmetries zones projections lung because of COVID-19; complications after firearm injury — pneumothorax; zones hyperthermia temporal bones due to contusion; vascular pattern disorders in the thyroid gland; functional and chronic disorders organs gastrointestinal and urological pathologies; degenerativedystrophic musculoskeletal changes The oscillographic distributions of temperature patterns of the detected pathological conditions, which characterize the severity of traumatic and degenerative-dystrophic changes, were studied. Conclusions. In the presented work for the first time obtained and the results of a comprehensive thermographic health check-up military personnel after a long stay in the combat zone and before operational Remote infrared thermography, as one of the methods of radiological diagnostics, allows for a comprehensive examination of a significant number of military personnel in a short period of time and to identify pathological changes that require additional examination by narrowly specialized specialists.